Penentuan Luas Lahan dengan Metode Pendekatan Lingkaran Berbasis Google Earth dan GADM untuk Wilayah Kabupaten Semarang - Windarni, Vikky Aprelia; Istiqomah, Dewi Anisa; Setiawan, Adi (Jurnal Transformatika, 2021)
Geographically Semarang regency as one of the regencies in Central Java province has an area of 95,020.67 hectares. In this study, the sub-district areas in Semarang regency is calculated using Circle Approach method and Karney s Polygon method using Google Earth and GADM database in the form of latitude and longitude coordinates. The results of the study show that the land area of 19 districts in Semarang regency is 11.61% more than of the reference areas based on the coordinates of the latitude and longitude on Google Earth using the circle approach method. While the percentage for the area referring to GADM data using the Karney s Polygon method is 9.71% more than of the reference areas and the difference is 13.55% more than the reference areas using Circle Approach. The results of the three comparisons show that GADM data using the Karney s Polygon method can produce better results than other methods.